MECHANISMS FOR INTEGRATING INTERNATIONAL EDUCATIONAL PROGRAMS INTO EARLY LITERACY PREPARATION OF PRESCHOOL CHILDREN - Guzal Qurbonova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article analyzes national and international experiences in preparing Early literacy preparation has become a strategic priority in contemporary preschool education due to its significant impact on children’s future academic achievement and lifelong learning outcomes. International educational programs have introduced innovative approaches that support the development of language, communication, pre-reading, and pre-writing competencies among preschool children. This article examines the mechanisms for integrating international educational programs into early literacy preparation in preschool settings. The study analyzes theoretical foundations, international best practices, and methodological approaches used in globally recognized educational frameworks, including Montessori, Reggio Emilia, HighScope, Creative Curriculum, and UNESCO-supported early childhood education initiatives. Particular attention is given to the pedagogical, technological, and organizational mechanisms that facilitate the development of literacy readiness among preschool children. The findings indicate that the integration of international educational programs contributes to enhanced phonological awareness, vocabulary development, emergent literacy skills, communication competence, and school readiness. Practical recommendations are proposed for adapting international experiences to local educational contexts while preserving cultural and linguistic identities.